The Feasibility of Developing Learning Devices Science Concept Based on Android for College Students in Elementary Teaching Program - Heny Sulistyaningrum; Sri Cacik; Anggun Winata; Mualifatul Munawaroh (Universitas Muhammadiyah Sidoarjo, 2021)
This research is motivated by efforts to improve scientific literacy skills and build the skills of 21st century students by developing the concept of Android-based science learning devices. Learning device are developed so that students can learn independently, quickly, practically, not limited by time and space, and students are ready to compete in the global world. This study aims to describe the feasibility of developing Android-based science learning tools for college students. This device was developed with a 4-D model by Thiagarajan. The tools developed are: RPP, e-book, LKM and evaluation tools. The research subjects were college UNIROW students who took the Science Concept 2018/2019 course. Collecting data using questionnaires and observations, then analyzed using descriptive statistical analysis techniques. From the results of the validation and test results, it can be concluded that the learning tools developed are categorized as good, valid and suitable for use in learning.